Odin Teatret’s The Tree: Performing in the Interstices - Patrick Campbell; Jane Turner (Revista Brasileira de Estudos da Presença, 2019)
This article aims to critically engage with Odin Teatret’s most recent addition to the repertoire, The Tree (2016), in order to investigate the ways in which Barba’s dramaturgical decision-making processes create a performance field that metaphorically comments on the status of the group today whilst critiquing contemporary geo-politics. Importantly, we argue that notions of interculturalism – which have often been employed by scholars to critique the Odin’s work – do not address the full complexity of the embodied concatenation of the group’s practice, and we employ the term interstitial to more effectively articulate the complex space produced by the group’s training and performances.